Prehospital shock index and systolic blood pressure are highly specific for pediatric massive transfusion. Issue 4 (October 2021) - Zhu, Caroline S.; Braverman, Maxwell; Goddard, Sabrina; McGinity, Ashley C.; Pokorny, Douglas; Cotner-Pouncy, Tracy; Eastridge, Brian J.; Epley, Sondra; Greebon, Leslie J.; Jonas, Rachelle B.; Liao, Lillian; Nicholson, Susannah E.; et al.
Abstract : BACKGROUND: While massive transfusion protocols (MTPs) are associated with decreased mortality in adult trauma patients, there is limited research on the impact of MTP on pediatric trauma patients. The purpose of this study was to compare pediatric trauma patients requiring massive transfusion with all other pediatric trauma patients to identify triggers for MTP activation in injured children. METHODS: Using our level I trauma center's registry, we retrospectively identified all pediatric trauma patients from January 2015 to January 2018. Massive transfusion (MT) was defined as infusion of 40 mL/kg of blood products in the first 24 hours of admission. Patients missing prehospital vital sign data were excluded from the study. We retrospectively collected data including demographics, blood utilization, variable outcome data, prehospital vital signs, prehospital transport times, and Injury Severity Scores. Statistical significance was determined using Mann-Whitney U test and χ 2 test. p Values of less than 0.05 were considered significant. RESULTS: Thirty-nine (1.9%) of the 2, 035 pediatric patients met the criteria for MT. All-cause mortality in MT patients was 49% (19 of 39 patients) versus 0.01% (20 of 1996 patients) in non-MT patients. The two groups significantly differed in Injury Severity Score, prehospital vital signs, and outcome data. Both systolic blood pressure (SBP) of <100 mm Hg and shock index (SI) of >1.4 were found to be highly specific for MT with specificities of 86% and 92%, respectively. The combination of SBP of <100 mm Hg and SI of >1.4 had a specificity of 94%. The positive and negative predictive values of SBP of <100 mm Hg and SI of >1.4 in predicting MT were 18% and 98%, respectively. Based on positive likelihood ratios, patients with both SBP of <100 mm Hg and SI of >1.4 were 7.2 times more likely to require MT than patients who did not meet both of these vital sign criteria. CONCLUSION: Pediatric trauma patients requiring early blood transfusion present with lower blood pressures and higher heart rates, as well as higher SIs and lower pulse pressures. We found that SI and SBP are highly specific tools with promising likelihood ratios that could be used to identify patients requiring early transfusion. LEVEL OF EVIDENCE: Therapeutic/care management, level V.